IMPLEMENTASI SUPERVISI KLINIS KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONAL GURU DI SMP NEGERI 12 KOLAKA UTARA - Arham, Arham; Lilianti, Lilianti; Yusuf, Ridwan (Universitas Wiralodra, 2025)
Education as a forum to produce a reliable generation and lead the development of modern educational technology. As a forum to produce a reliable generation, teachers are required to have professional quality in their professional fields. The professional behavior of teachers is very important for the learning process, but there are still many problems related to teacher professionalism, especially at SMP Negeri 12 North Kolaka, namely there are still teachers who teach with conventional methods and lack innovative learning media. Teachers' ability to prepare learning tools such as lesson plans, syllabus, and assessment instruments still needs to be improved, teachers' motivation to develop themselves through professional development activities is still low. And the implementation of clinical supervision by school principals has not been running optimally and systematically. This study aims to analyze the planning, implementation and evaluation and follow-up of clinical supervision carried out by school principals in improving teacher professionalism at SMP Negeri 12 North Kolaka. The method used in this study is through a qualitative approach with a case study design with data collection techniques through interviews, direct observation, and document analysis. The results of the study show that clinical supervision applied by school principals plays an active role in providing constructive feedback to teachers, as well as creating an environment that supports professional development. In addition, this study also identifies several challenges faced in the supervision process, such as time constraints and lack of training for principals and teachers. Nonetheless, the results suggest that effective implementation of clinical supervision can contribute significantly to improving teacher competence and performance.